Antioxidant and Antifungal Activity of Jeringau (Acorus calamus L.) Extract In Some Organic Solvents In Vitro - Muchtaromah, Bayyinatul; Ahmad, Mujahidin; Hasan, M. Nur; Wahyudi, Didik (El-Hayah : Jurnal Biologi, 2017)
Candidiasis is one disease that has experienced by 75% of women in Indonesia caused by fungal infection,Candida albicans. Candidiasis can cause serious complications such as infertility. One of the best known ingredients to cure infertility problems is jeringau rhizome (Acoruscalamus L.). This research is the first step to process for Â standardization and scientification of jeringau rizhome as one of the basic ingredients of Madura traditional medicine, jamu "SuburKandungan". It was aimed to investigate antioxidant and antifungal activity of jeringau rizhome in some organic solvents. Samples were extracted by maceration method using ethanol, chloroform, and n-hexane. Antioxidant activityassaywas determined using DPPH method.Ascorbic acid was used as control. Â Antifungal activity test on Candida albicans was done by usingkirby bauer method to measure diameter of inhibition zone and microdilution plate method to determine MIC and MFC. The highest antioxidant activity was revealed by ethanolfollowed by chloroform and n-hexane, while the highest antifungal activity was obtained by ethanol followed by n-hexane and chloroform. The MIC value of ethanol, chloroform and n-hexanewere founded at concentration of 0.39% and the MFC at a concentration of 0.78%.